Vortex-induced vibration energy harvesting with tandem square bluff bodies: Spacing ratio effects - Yuansheng Chen; Zheng Qi; Hongli Ji; Jianzhou Du; Pengcheng Zhao; Longting Li (AIP Advances)
The horizontal (L/D) and vertical H/D) spacing ratios of square bluff bodies are critical parameters influencing the efficiency of vortex-induced vibration (VIV) wind energy harvesting. This study investigates a tandem stationary square bluff body (SSBB) and a vibrating square bluff body under various spacing configurations using ANSYS/FLUENT simulations. The results show that without SSBB, the root-mean-square (RMS) voltage generated by the piezoelectric patches increases consistently with wind speed. However, with SSBB, RMS voltage initially decreases and then increases as L/D rises, reaching a minimum at L/D = 4.5. At optimal configurations (L/D = 6.5, H/D = 0.5) and a wind speed of 9 m/s, the RMS voltage achieves a maximum value, improving by 34.43% compared to the configuration without SSBB. Experimental validation confirms the simulation results. This finding will be a significant fundamental for future design of VIV wind energy harvesting devices.